Properties of Briquettes from Paper Waste - Brozek, Milan (Manufacturing Technology Journal, 2013)
Worldwide increasing energy demand is today permanently covered by a majority of non-renewable energy sources, namely by coal, crude oil and natural gas. This causes the rapid decline of their reserves and the time gets near when they will be run out. Therefore in last years the exploitation of renewable energy sources is permanently preferred. One of alternative fuel forms is the fuel on the basis of paper waste. In this paper the results of tests are published, which were carried out using five sorts of paper waste, pressed in form of briquettes. During the tests following briquettes parameters were watched: moisture content, ash amount, length and diameter, weight, density, rupture force and mechanical durability. The results are presented in form of tables and graphs. It was proved that briquettes made from recovered paper and board are compared with briquettes from wood waste of high density, high mechanical durability and for their rupture the relatively high force is necessary. But at the same time they have high ash amount and low combustion heat.
Keywords: renewable energy sources; recovered paper and board; briquetting; properties of briquettes; mechanical durability